New genes important for development. (10th April 2014) - Kemkemer, Claus; Long, Manyuan
<x xml:space="preserve">Abstract</x> The genomic revolution and new sequencing technologies are allowing scientists to pick apart the origin of new genes and how they assume vital roles in development, despite their absence from perfectly viable ancestral species. <boxed-text content-type="graphic" id="embr201438787-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text>